2020
DOI: 10.1111/psyp.13533
|View full text |Cite
|
Sign up to set email alerts
|

Task‐switching costs have distinct phase‐locked and nonphase‐locked EEG power effects

Abstract: Event‐related potentials (ERPs) and total time–frequency power analyses have shown that performance costs during task switching are related to differential preparation to switch tasks (switch cost) and repeat the same task (mixing cost) during both proactive control (cue‐to‐target interval; CTI) and reactive control (post‐target). The time–frequency EEG signal is comprised of both phase‐locked activity (associated with stimulus‐specific processes) and nonphase‐locked activity (represents processes thought to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 68 publications
3
20
0
Order By: Relevance
“…One of the reasons is that the subtraction of the evoked activity from TSE activity to obtain the induced activity is assuming that evoked activities are stable in time across trials. Therefore, future studies have to be performed to confirm the present results with different procedures described by other authors [34] to control for the possibility of jitter effects biasing induced activity.…”
Section: Plos Onementioning
confidence: 57%
“…One of the reasons is that the subtraction of the evoked activity from TSE activity to obtain the induced activity is assuming that evoked activities are stable in time across trials. Therefore, future studies have to be performed to confirm the present results with different procedures described by other authors [34] to control for the possibility of jitter effects biasing induced activity.…”
Section: Plos Onementioning
confidence: 57%
“…This study analysed data from the Age‐ility Project (Karayanidis et al, 2016), using the same dataset as McKewen et al (2020). Age‐ility participants were recruited from a range of sources, including secondary and tertiary education centres, community organisations and local businesses.…”
Section: Methodsmentioning
confidence: 99%
“…As discussed above, previous cued‐trials task‐switching literature has shown effects of switching and mixing tasks at both frontal and parietal sites. Based on our previous work in the same dataset (McKewen et al, 2020), FCz and Pz were chosen as the seeds for ISPC analyses in order to capture frontal and parietal networks. Based on previous connectivity analyses in cued‐trials task‐switching (Cooper et al, 2015; Lopez et al, 2019; Sauseng, Klimesch, Schabus, & Doppelmayr, 2005), and previous analyses of this dataset (McKewen et al, 2020), we focussed on ISPC analyses on theta activity (defined as 4–8 Hz).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the mixing cost, we are aware of only two previous studies 1 examining brain oscillations associated 1 During the revision process, we found out another very recent timefrequency study comparing switch and mixing costs (McKewen et al, 2020). We report it here for the reader's benefit.…”
mentioning
confidence: 95%